Improving marketability and quality of Sulemu soy milk: A community engagement approach to product diversification - Rahayu, Triastuti; Nurcahyanto, Guntur; Aryani, Ima; Suryani, Titik; Tyastuti, Erma Musbita; Sari, Siti Kartika; Maimun, Muhammad Halim; Ripdianti, Arum Dyah; Hardianto, Alden Ganendra Madhava Priya (Universitas Muhammadiyah Magelang, 2025)
Original